228k views
5 votes
What should your first step look like when solving this system by substitutiony=2x-6-3x+4y=-12

What should your first step look like when solving this system by substitutiony=2x-example-1

1 Answer

2 votes

The first equation is already solved for y.

So, our logical first step to solve this equation would be to substitute the first equation into the second equation.

So, we'll have:


\begin{gathered} y=2x-6 \\ -3x+4y=-12 \\ \text{Substituting 1st equation in 2nd one:} \\ -3x+4(2x-6)=-12 \end{gathered}

This is the logical first step.

User Lakatos Gyula
by
5.9k points